Teks Sastra Sebagai Media Komunikasi Antarbangsa (Kajian Atas Novel Dari Fontenay Ke Magallianes Karya Nh. Dini) - Tuti Kusniarti (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2010)
This novel is one form of communication between nations conducted by the author with her readers. The storytelling technique used by NH Dini is narrative that invites the reader to indirectly see and be involved in describing the story. As an author, NH Dini is so straightforward in telling the story which is played by the main character who does not forget the background of Javanese culture and love the second homeland France. From Fontenay to Magalliances is an expression of the author about how should a woman who grew up in a cultural environment of Java can still coexist with the people around her without losing her identity as a foreigner in the second homeland. Communication that occurs between the characters is a form of communication between nations that is no longer so accentuate each other's culture and remaining respectful. In this case, the main character can still be a wife to her French husband without having to change her appearance and lifestyle, although the internal communication between them is no longer in harmony, but as Javanese woman, Dini still keeps their relationship in front of their relatives. Key words: literary text, communication, intra-nations